محاولة التيسير في تدريس النحو العربي - جـ سوتارجو (CMES (Center of Middle Eastern Studies), 2016)
By using Arabic language, Allah SWT had been sent the holy Qur‟an as the roles for the human being in the worship and the process of interaction with the mankind in the life. To gain the message of Al-Qur‟an deeply and comprehensively, the student should learn specifically for the sciences which had the purposes to understand Arabic language as the main medium for understanding the holy Qur‟an. The Arabic Syntax (Nahwu) is one of the sciences needed for understanding comprehensively about the sentences used in the Al-Qur‟an. The students have to understand the sentences before understanding the contents of Al-Qur‟an passing through the sentences in Al-Qur‟an. In the process of learning Nahwu, there are some items which had been mastered beforem completely, and it should need the simplification and facilitation in the process of learning. Finally, the process of teaching and learning should pass through some elements, correlated with the contents or teaching methodology.